2013
DOI: 10.1016/j.nuclphysb.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Parton distributions with QED corrections

Abstract: We present a set of parton distribution functions (PDFs), based on the NNPDF2.3 set, which includes a photon PDF, and QED contributions to parton evolution. We describe the implementation of the combined QCD+QED evolution in the NNPDF framework. We then provide a first determination of the full set of PDFs based on deep-inelastic scattering data and LHC data for W and Z/γ * Drell-Yan production, using leading-order QED and NLO or NNLO QCD. We compare the ensuing NNPDF2.3QED PDF set to the older MRST2004QED set… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
568
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 563 publications
(572 citation statements)
references
References 84 publications
4
568
0
Order By: Relevance
“…Here, in the QCD improved calculations µ 2 F = m 2 t was used as the factorization scale. Let us show also our predictions obtained with the NNPDF2.3 QED photon distributions [38], (see figure 11). In the left panel of figure 11 we concentrate on the biggest inelastic-inelastic contribution.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Here, in the QCD improved calculations µ 2 F = m 2 t was used as the factorization scale. Let us show also our predictions obtained with the NNPDF2.3 QED photon distributions [38], (see figure 11). In the left panel of figure 11 we concentrate on the biggest inelastic-inelastic contribution.…”
Section: Resultsmentioning
confidence: 92%
“…Recently the NNPDF collaboration presented a detailed study of uncertainties of a photon PDF in the framework of so-called neural network PDFs [38]. This analysis suggests that inelastic photon-induced contributions may have rather big uncertainies.…”
Section: Jhep02(2015)098mentioning
confidence: 99%
“…[2]. interface for the visualization of PDFs with a wide range of formats: absolute plots, ratio plots, compare PDFs from different groups, compare error PDF from a single set, plot all PDF flavor combinations at the same time, compute parton luminosities and finally compute also DIS structure functions and APPLgrid observables.…”
Section: Resultsmentioning
confidence: 99%
“…Even though demonstrated only at a qualitative level, an increase of the gluon density at small-x values tends to be preferred for a consistent description of measurements at central and forward pseudorapidities. In particular, it has been observed that the description of charged-particle multiplicity at high pseudorapidities [17] provided by tunes using the NNPDF2.3LO PDF [18], e.g. Monash [19] and CUETP8M1 [17], is better than tunes using other PDF sets.…”
Section: Small-x Gluon Studiesmentioning
confidence: 99%